Quantitative evaluation of local pulmonary distribution of TiO2 in rats following single or multiple intratracheal administrations of TiO2 nanoparticles using X‐ray fluorescence microscopy. Issue 10 (16th February 2016) - Zhang, Guihua; Shinohara, Naohide; Kano, Hirokazu; Senoh, Hideki; Suzuki, Masaaki; Sasaki, Takeshi; Fukushima, Shoji; Gamo, Masashi
Abstract: Uneven pulmonary nanoparticle (NP) distribution has been described when using single‐dose intratracheal administration tests. Multiple‐dose intratracheal administrations with small quantities of NPs are expected to improve the unevenness of each dose. The differences in local pulmonary NP distribution (called microdistribution) between single‐ and multiple‐dose administrations may cause differential pulmonary responses; however, this has not been evaluated. Here, we quantitatively evaluated the pulmonary microdistribution (per mesh: 100 μm × 100 μm) of TiO2 in lung sections from rats following one, two, three, or four doses of TiO2 NPs at a same total dosage of 10 mg kg −1 using X‐ray fluorescence microscopy. The results indicate that: (i) multiple‐dose administrations show lower variations in TiO2 content (ng mesh −1 ) for sections of each lobe; (ii) TiO2 appears to be deposited more in the right caudal and accessory lobes located downstream of the administration direction of NP suspensions, and less so in the right middle lobes, irrespective of the number of doses; (iii) there are not prominent differences in the pattern of pulmonary TiO2 microdistribution between rats following single and multiple doses of TiO2 NPs. Additionally, the estimation of pulmonary TiO2 deposition for multiple‐dose administrations imply that every dose of TiO2 would be randomly deposited only in part of the fixed 30–50% of lung areas. The evidence suggests that multiple‐dose administrations do not offer remarkable advantages over single‐dose administration on the pulmonary NP microdistribution, although multiple‐dose administrations may reduce variations in the TiO2 content for each lung lobe. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We quantitatively evaluated the pulmonary microdistribution (per mesh: 100 μm × 100 μm) of TiO2 in lung sections from rats following one, two, three, or four doses of TiO2 NPs at a same total dosage of 10 mg kg −1 using X‐ray fluorescence microscopy. The evidence suggests that multiple‐dose administrations do not offer remarkable advantages over single‐dose administration on the pulmonary NP microdistribution, although multiple‐dose administrations may reduce the variations in TiO2 content for each lung lobe.